Impact of gut microbiome on serum IgG4 levels in the general population: Shika-machi super preventive health examination results - Koshida, Aoi; Karashima, Shigehiro; Ogura, Kohei; Miyajima, Yuna; Ogai, Kazuhiro; Mizoguchi, Ren; Ikagawa, Yasuo; Hara, Satoshi; Mizushima, Ichiro; Fujii, Hiroshi; Kawano, Mitsuhiro; Tsujiguchi, Hiromasa; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
This is a provisional file, not the final typeset article Introduction: Immunoglobulin G4 (IgG4) is a member of the human immunoglobulin G (IgG) subclass, a protein involved in immunity to pathogens and the body's resistance system. IgG4-related diseases (IgG4-RD) are intractable diseases in which IgG4 levels in the blood are elevated, causing inflammation in organs such as the liver, pancreas, and salivary glands. IgG4-RD are known to be more prevalent in males than in females, but the etiology remains to be elucidated. This study was conducted to investigate the relationship between gut microbiota (GM) and serum IgG4 levels in the general population. Methods: In this study, the relationship between IgG4 levels and GM evaluated in male and female groups of the general population using causal inference. The study included 191 men and 207 women aged 40 years or older from Shika-machi, Ishikawa. GM DNA was analyzed for the 16S rRNA gene sequence using next-generation sequencing. Participants were bifurcated into high and low IgG4 groups, depending on median serum IgG4 levels. Results: ANCOVA, Tukey's HSD, linear discriminant analysis effect size, least absolute shrinkage and selection operator logistic regression model, and correlation analysis revealed that Anaerostipes, Lachnospiraceae, Megasphaera, and [Eubacterium] hallii group were associated with IgG4 levels in women, while Megasphaera, [Eubacterium] hallii group, Faecalibacterium, Ruminococcus.1, and Romboutsia were associated with IgG4 levels in men. Linear non-Gaussian acyclic model indicated three genera, Megasphaera, [Eubacterium] hallii group, and Anaerostipes, and showed a presumed causal association with IgG4 levels in women. Discussion: This differential impact of the GM on IgG4 levels based on sex is a novel and intriguing finding.